2005
DOI: 10.7547/0950410
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Gastrocnemius Recession for the Treatment of Gastrocnemius Equinus

Abstract: A prospective analysis was conducted of the amount of correction obtained and number of complications resulting from 31 endoscopic gastrocnemius recessions in 28 patients. The average amount of increase in ankle dorsiflexion was 18 degrees. Few complications were encountered, with mild "soreness" and distal "bruising" being reported by four patients. The only other complaint was "weakness." The endoscopic gastrocnemius recession is a minimally invasive technique with a low rate of complications that offers a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 12 publications
1
15
0
2
Order By: Relevance
“…Significant pain relief and high satisfaction rates were reflected by improvements in the VAS score and either good or very good outcomes on the Likert scale. These results are consistent with those from other studies in the current literature[12,13]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Significant pain relief and high satisfaction rates were reflected by improvements in the VAS score and either good or very good outcomes on the Likert scale. These results are consistent with those from other studies in the current literature[12,13]. …”
Section: Discussionsupporting
confidence: 94%
“…Complications of gastrocnemius recession has been well documented in the literature[12]. Of these, the potential for significant plantarflexion weakness attributed to lengthening of the gastroc-soleus muscle unit[13] has generated much concern amongst orthopaedic surgeons and sports medicine practitioners alike.…”
Section: Introductionmentioning
confidence: 99%
“…Schroeder [17] only had a 16°i ncrease in ankle dorsiflexion after endoscopic GSR while another study reported a 13°increase in dorsiflexion [19]. Additionally, DiDomenico et al [5] accomplished an 18°g ain in dorsiflexion after endoscopic GSR. These studies however did not examine patients undergoing tibial lengthening [5,16,17], and so the difference in etiology and timing of onset of gastrocsoleus contracture may have played a role in the different outcomes.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, DiDomenico et al [5] accomplished an 18°g ain in dorsiflexion after endoscopic GSR. These studies however did not examine patients undergoing tibial lengthening [5,16,17], and so the difference in etiology and timing of onset of gastrocsoleus contracture may have played a role in the different outcomes. The patients in the study of Saxena and Widtfeldt [16] received an endoscopic GSR for preexisting contractures secondary to multiple etiologies, while the studies of Schroeder [17] and DiDomenico et al [5] did not define the etiology of the contracture in their patient populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation